Comparing the Effect of Leaf Spring and Swedish AFO in Patient with Drop Foot Deformity (Peroneal Nerve Injury) - Khan, Muhammad Kamran; Bibi , Uzma; Shah , Wisal (Poltekkes Kemenkes Jakarta I, 2023)
Background: Injection-molded polypropylene splint in Swedish AFO provides static dorsiflexion assistance and lateral stability for the entire foot-ankle area. It prevents foot drop while walking. Purpose: Comparing the effect of leaf spring and Swedish AFO in patient with drop foot deformity (Peroneal nerve injury). Objectives: To determine better controlling of planter flexion during Initial contact and Mid Swing of the Gait. Methodology: Four (4) participants with Drop Foot (Peroneal nerve injury) were selected through simple random sampling and they were allowed to walk at their self-selected speed with Swedish AFO and with PLS AFO in order to compare their controlling of Planter Flexion at Initial Contact and at Mid Swing under experimental design. The study is conducted at Pakistan Institute of Prosthetic and Orthotic Sciences Peshawar. Paired sample “t” test is used to compare the result. Results: By observing both the AFO’s i.e. Swedish AFO and Posterior Leaf Spring AFO at Initial Contact Phase of the Gait the deviation’s results for Swedish AFO’s are 3.82, 4.40, 11.22 and 9.18 degrees and deviations results for Posterior Leaf Spring AFO’s are 2.32, 3.34, 8.71 and 8.53 degrees. Statistical results implied that the impact of Leaf Spring AFO is bigger than Leaf spring AFO. Conclusion: Posterior leaf Spring AFO is more effective design for Persons with Drop foot (Peroneal nerve injury) as compare to Swedish AFO.